ADOPSI TEKNOLOGI BUDIDAYA SORGUM DI DESA PONCOSARI KECAMATAN SRANDAKAN KABUPATEN BANTUL - Nurkholipah Nurkholipah; Subejo Subejo; Harsoyo Harsoyo (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2015)
Technology adoption is a process by someone of knowing until starting to apply the technology. Development is the process of improving the quantity and quality. The purpose of this research was to: (1) identify the developmentof sorghum cultivation, (2) determine the adoption level of sorghum cultivation technology, (3) determine the factors that influence to adoption level of sorghum cultivation technology, and (4) determine the effect of adoption level and the other factors in development of sorghum cultivation. The research was conducted in Poncosari Village, Srandakan Sub-district, Bantul District. The samples were farmers who directly involved in the sorghum cultivation in productive land (irrigated land). The basic method used descriptive analytic by using census sampling method that consist of 30 sorghum farmers who were members of Bismo Farmer Groups. Data were analyzed by a qualitative and quantitative approaches. Quantitative data at thefirst hypothesis was analyzed with proportion test, the second and third hypothesis used multiple linear regression. The research results showed that most of the sorghumfarmers (70%) had a high adoption level of sorghum cultivation technology. Based on the results ofmultiple linear regression analysis, factors that positivelyinfluenced to adoption level of sorghum cultivation technology were land size and role offarmer group. Development ofsorghum cultivation was included in low category with factors that positively influenced was motivation of farmers.